1972
DOI: 10.1073/pnas.69.8.2015
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Terminal Sequences and Sites of In Vivo Acetylation of Trout-Testis Histones III and IIb 2

Abstract: The sequences of the first 25 residues of histone III, and the first 22 residues of histone Ib2, from trout testis have been determined on an automatic protein sequencer. The amino-terminal sequence of trout-testis histone III is identical to the corresponding region of calfthymus histone III, whereas the trout-testis histone IIb2 sequence differs from that of calf-thymus histone 11b2 at several positions in the amino-terminal region. Several in vivo sites of acetylation of these trout-testis histones have als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The precise role of histone acetylation in chromosome replication is not clear. Dixon suggested acetylation may be required for correct assembly of histones and DNA (Candido & Dixon, 1972). More recently, Seale (1981) has shown that nucleosomes containing newly synthesized histones are more salt labile than mature nucleosomes, consistent with the binding scheme proposed by Dixon and the presence of acetylation in all core histones.…”
Section: Discussionmentioning
confidence: 53%
“…The precise role of histone acetylation in chromosome replication is not clear. Dixon suggested acetylation may be required for correct assembly of histones and DNA (Candido & Dixon, 1972). More recently, Seale (1981) has shown that nucleosomes containing newly synthesized histones are more salt labile than mature nucleosomes, consistent with the binding scheme proposed by Dixon and the presence of acetylation in all core histones.…”
Section: Discussionmentioning
confidence: 53%
“…Historically in rainbow trout, and recently in the zebrafish model, histone marks have also been studied in the context of intergenerational transfer. In rainbow trout, somatic cell histones have been shown to be retained in spermatogenesis where they undergo acetylation, as demonstrated for H2B, H3 and H4 (Candido and Dixon, 1971;Candido and Dixon, 1972;Christensen et al, 1984), methylation, as shown for H3 and H4 (Honda et al, 1975) and phosphorylation, as identified for H2B, H3 and H4 (Sung and Dixon, 1970). As in rainbow trout (Avramova et al, 1983), DNA material in zebrafish sperm is packaged in nucleosomes containing somatic histones and histone variants, which is in contrast to the situation in mammals, where genetic material is packaged by protamines (Wu et al, 2011).…”
Section: A C C E P T E D Mmentioning
confidence: 97%
“…Acetylated forms of histones have been found during spermatogenesis in various species including, trout [56], rat [57] and rooster [58]. The use of antibodies, specifically recognizing individual acetylated residues, has allowed a more precise characterization of histone acetylation pattern during spermatogenesis [59].…”
Section: Histone Acetylationmentioning
confidence: 99%